Morphology, phylogeny, growth rate and nodularin production of Nodularia spumigena from Brazil. Issue 10 (26th November 2017) - da Silveira, Savênia Bonoto; Wasielesky, Wilson; Andreote, Ana Paula Dini; Fiore, Marli Fatima; Odebrecht, Clarisse
ABSTRACT: Blooms of the toxic cyanobacterium Nodularia spumigena occur in various locations worldwide, but have not been observed in Brazil until recently. Three Nodularia strains were isolated from summer blooms in experimental shrimp production ponds of Penaeus vannamei in Rio Grande, in southern Brazil; these strains were characterized by morphology, phylogeny, growth rate and toxicity. The strains were identified as N. spumigena based on the size of vegetative cells, heterocytes and akinetes under a light microscope and based on the number of gas vesicles per μm 2 under a transmission electron microscope. The 16S rRNA gene sequences of the three strains showed high identity (> 99%) with N. spumigena sequences available on the NCBI database but were grouped closer in the phylogenetic tree with N. spumigena strains from Australia and USA than those from the Baltic Sea. The growth rate in batch culture varied between 0.2 and 0.6 μ d −1 based on cell density, optical density and chlorophyll-a content. The three strains produced the hepatotoxin nodularin (ELISA plate kit) with similar toxicity values (4.8–4.9 µg l −1 ). We conclude that the three isolated strains are N. spumigena with similar rates of growth and nodularin production. The presence of N. spumigena now represents a potential problem in aquaculture and estuarine environments in Brazil.